2009
DOI: 10.1007/s10571-009-9365-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antioxidant Treatment in Global Ischemia and Ischemic Postconditioning in the Rat Hippocampus

Abstract: Ischemic postconditioning is a very effective way how to prevent delayed neuronal death. Effect of Ginkgo biloba extract (EGb 761; 40 mg/kg) posttreatment was studied on the rat model of transient forebrain ischemia and ischemia/postconditioning. Global ischemia was produced by four-vessel occlusion in Wistar male rats. Two experimental protocols were used: (a) 10 min of ischemia/7 days of reperfusion with or without EGb 761 treatment or (b) 10 min of ischemia/2 days of reperfusion/5 min of ischemia (postcondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…This same mechanism may underlie the Post C induction of NR2A phosphorylation observed in our study, as we have found that Post C rapidly enhances NADPH oxidase activity in the CA1 region and that administration of an NADPH oxidase inhibitor blocks Post C neuroprotection (Zhang G, Wang R, Brann D, unpublished observation). In support of this mechanism, Burda and coworkers (Domorakova et al, 2009), previously reported that administration of an antioxidant prevents Post C neuroprotection.…”
Section: Discussionmentioning
confidence: 85%
“…This same mechanism may underlie the Post C induction of NR2A phosphorylation observed in our study, as we have found that Post C rapidly enhances NADPH oxidase activity in the CA1 region and that administration of an NADPH oxidase inhibitor blocks Post C neuroprotection (Zhang G, Wang R, Brann D, unpublished observation). In support of this mechanism, Burda and coworkers (Domorakova et al, 2009), previously reported that administration of an antioxidant prevents Post C neuroprotection.…”
Section: Discussionmentioning
confidence: 85%
“…Although our data do not allow us to delineate the mechanism by which this pre-conditioning is occurring, it may be mediated by an LCAR-dependent increase in anti-oxidant enzyme capacity. Studies have demonstrated that mild ischemia can upregulate SOD1, SOD2 and catalase in hippocampal tissue [29], [30]. Blocking this effect with an antisense to SOD1 significantly decreases the neuroprotective effect [31], [32], [33].…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate the protective effect of ischemic post-conditioning and are consistent with findings from previous studies. [17][18][19] Both ischemic pre-conditioning (I PreC) and I PostC have protective effects against cerebral ischemia reperfusion injury. [20][21][22] However, I PreC is impractical as a clinical protective treatment because the onset of cerebral ischemia is unpredictable.…”
Section: Discussionmentioning
confidence: 99%